Blending Learning, Bridging Cultures: Coil For Efl Speaking And Writing - Retimi, Chiraz.retimi; Boukhechba, Hicham (Eddissi Languages Journal, 2025)
As the cognizance of living in a globalized world intensifies, the need to foster both intercultural competence and productive skills in English as a Foreign Language (EFL) classrooms has become increasingly urgent. Linguistic proficiency alone is not sufficient to navigate the complexities of this interconnected world; therefore, fostering an ability to move from a state of monoculturalism to bi- or multi-culturalism should be a priority for EFL teachers (Damen, 1987). As a natural consequence of current technological advancements, blended learning emerges as an innovative teaching approach that combines face-to-face and online language instruction for maximum learner engagement. This paper intends to explore how Collaborative Online International Learning (COIL) Programs, as a form of blended learning, promote meaningful intercultural communication to improve learners’ speaking and writing skills ultimately. By integrating online blogs for reflective writing and video conferencing for real-time cross-cultural discussions, this COIL-based blended learning model creates authentic communicative opportunities while fostering the learners’ productive skills. This paper offers a conceptual exploration, drawing on existing literature and theoretical perspectives to examine the pedagogical implications of COIL models and their potential to position EFL learners as global citizens who understand the nuances of intercultural encounters and articulate their thoughts with clarity and accuracy in both writing and speaking communication.